Influence of growth time on crystalline structure, conductivity and optical properties of ZnO thin films - Benramache, Said; Chabane, Foued; Benhaoua, Boubaker; Lemmadi, Fatima Z (IOP Publishing, 2013)
This paper examines the growth of ZnO thin films on glass substrate at 350 °C using an ultrasonic spray technique. We have investigated the influence of growth time ranging from 1 to 4 min on structural, optical and electrical properties of ZnO thin films. The as-grown films exhibit a hexagonal structure wurtzite and are (002) oriented. The maximum value of grain size G = 63.99 nm is attained for ZnO films grown at 2 min. The average transmittance is about 80%, thus the films are transparent in the visible region. The optical gap energy is found to increase from 3.26 to 3.37 eV with growth time increased from 1 to 2 min. The minimum value of electrical resistivity of the films is 0.13 Ω·cm obtained at 2 min. A systematic study on the influence of growth time on the properties of ZnO thin films deposited by ultrasonic spray at 350 °C has been reported.
Article
Keywords: ZnO; thin film; growth time; ultrasonic spray technique